PRELIMINARY LIST OF INFRARED STARS - CHAVIRA, E (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1968)
Extremely red stars were identified by overlaying red and infrared plates taken consecutively and during the same night. We present a preliminary list, with finding charts, of those objects of I - R > 3.0 mag. The data were obtained at the Tonantzintla Sc
BOL OBS TONAN TACUB
Keywords: PRELIMINARY LIST, INFRARED STARS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS